BAHASA ALAY PADA REMAJA PERUMAHAN KRAMAT JATI JAKARTA TIMUR - Nadya Mayangsari; Somadi Sosrohadi; Tadjuddin Nur (Universitas Negeri Makassar, 2023)
Alay Language in Youth Housing Kramat Jati, East Jakarta. This study aims to determine the effect of using Alay on adolescents in the Kramat Jati housing complex, East Jakarta. This research uses a qualitative research method through descriptive analysis techniques. The subjects in this study were teenagers in the Kramat Jati housing complex, East Jakarta. With this method, data is collected and presented in the form of words. In this study, data were obtained on the speech of the Alay language at Kramat Jati housing, East Jakarta. The data obtained for further analysis will depend on the focus of the research. The results of the study show that the use of Alay has a negative impact on the proper and correct use of Indonesian.